The role of G protein-coupled receptor 35 in pancreatic cancer - Kim, Minkyoung (Curtin University, 2020)
This PhD thesis discusses the novel therapeutic target of PDAC, which is GPR35. For the first time, we have characterized its diverse roles controlling apoptosis, autophagy, cell cycle arrests, migration and invasion in PDAC cells. In addition, this work provides its related signalling pathways which are AKT and HIF-1. Our investigation of GPR35 in PDAC has contributed to suggest a new therapeutic strategy to cure pancreatic cancer patients.